2019
DOI: 10.1111/jpn.13190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary saponin rich soapnut (Sapindus mukorossi) shell powder on growth performance, immunity, serum biochemistry and gut health of broiler chickens

Abstract: This study was conducted to evaluate the effects of dietary soapnut (Sapindus mukorossi) shell powder (SSP), a cheap source of saponins, on growth performance, immunity, serum biochemistry and gut health of broiler chickens. The experimental design was 4×2, employing four saponin levels (0, 100, 150 and 200 mg/kg diet), each provided for two time durations (0–42 day and 21–42 day) resulting into eight dietary treatments. Results revealed no significant effect of dietary saponins on body weight gain, feed intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Moreover, the immunomodulatory function of plant polyphenol has been reported via dropping the expression of interleukins IL-4, IL-13, IL-18 and IFN-γ in LPS challenged broilers fed with phenolic rich diets [ 86 ]. Dietary supplementation of saponins, phenolic compounds originated from soapnut ( Sapindus mukorossi ) at 150 mg/kg could improve the cell-mediated and humoral immune response of broilers without adverse effects on optimum body weight [ 87 ]. Inclusion of thyme essential oil at 3 g/kg could improve serum IgG, IgA, antibody titer against ND vaccine in broilers and could eliminate the adverse effects of ochratoxin A and aflatoxin B 1 in broiler diets [ 88 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the immunomodulatory function of plant polyphenol has been reported via dropping the expression of interleukins IL-4, IL-13, IL-18 and IFN-γ in LPS challenged broilers fed with phenolic rich diets [ 86 ]. Dietary supplementation of saponins, phenolic compounds originated from soapnut ( Sapindus mukorossi ) at 150 mg/kg could improve the cell-mediated and humoral immune response of broilers without adverse effects on optimum body weight [ 87 ]. Inclusion of thyme essential oil at 3 g/kg could improve serum IgG, IgA, antibody titer against ND vaccine in broilers and could eliminate the adverse effects of ochratoxin A and aflatoxin B 1 in broiler diets [ 88 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, serum TG concentrations were generally lower in yak calves consuming the herbal extracts, especially G. uralensis , than in control yak calves. Previous studies reported that administration of G. uralensis reduced hepatic TG levels in mice [ 23 ], while consuming saponins reduced serum TG concentrations in sheep and chickens [ 24 , 25 ]. Furthermore, ursolic acid, the main component of saponins (terpene) in G. uralensis , alleviated lipid accumulation by activating the AMPK signaling pathway [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The microbial colony counting was done between 24 and 48 hr after incubation using a Quebec colony counter. The CFU were defined as distinct colonies measuring at least 1 mm in diameter and expressed as log 10 CFU per g sample (Bera et al ., 2019). CFUnormalg1=false(Total0.166667emno.0.277778emof0.277778emcolonies0.277778emcounted0.166667em×0.277778emDilution0.277778emfactorfalse)/Volumeofaliquottaken.…”
Section: Methodsmentioning
confidence: 99%
“…The microbial colony counting was done between 24 and 48 hr after incubation using a Quebec colony counter. The CFU were defined as distinct colonies measuring at least 1 mm in diameter and expressed as log 10 CFU per g sample (Bera et al, 2019).…”
Section: Gut and Faecal Microbiologymentioning
confidence: 99%